ACCULTURATION OF LOCAL CULTURE AND RELIGION IN THE LEK-LEK-AN TRADITION IN THE SEI KEPAYANG ASAHAN COMMUNITY - Julaikha Julaikha; Edi Safri; Taufiqurrahman Taufiqurrahman; Edriagus Saputra (Al-Qalam, 2021)
This research is a form of living hadith study that discusses the acculturation of local culture and religion in implementing the lek-lekan tradition in the Sei Kepayang community, Asahan Regency, North Sumatra. This study used a descriptive qualitative method with an ethnographic approach. The data were collected through observation, interviews, and documentation. The informants were the government, ulama, community leaders, event organizers and the Sei Kepayang community in general. The results of this study showed the tradition of lek-lek-an carried out at the birth of a baby by arranging an event at the place of the baby's parents. The tradition of lek-lekan is completed with an aqeeqah ceremony for the baby. The primary foundation for the community in carrying out the tradition of lek-lekan is to pass down the traditions of the local community continuously and the sunnah of the Prophet Muhammad related to the aqeeqah of a newborn child.